Examining Ethical Decision-Making, Transparency Initiatives, and Risk Management Strategies in the Nonprofit Sector - Tyagi, Vaibhav (Journal of Advanced Research in Nonprofit Organizational Governance and Social Impact Measurement, 2025)
Nonprofit organizations play a crucial role in addressing societal issues, and their ability to effectively execute their missions is closely tied to strong governance, ethical decision-making, transparency, and risk management practices. This article explores the ethical frameworks nonprofits adopt, initiatives to enhance transparency, and the strategies employed to manage risks. By analyzing various case studies and practices within the nonprofit sector, this review seeks to provide a comprehensive overview of how these elements contribute to accountability and sustainable organizational growth. Ethical decision-making processes ensure that nonprofit leaders act in the best interest of the communities they serve, while transparency initiatives foster trust and donor confidence. Simultaneously, effective risk management strategies help nonprofits navigate uncertainties, allowing them to fulfill their missions without jeopardizing their operations.